2018
DOI: 10.1080/22797254.2018.1533793
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring long-term forest dynamics with scarce data: a multi-date classification implementation in the Ecuadorian Amazon

Abstract: Monitoring long-term forest dynamics is essential for assessing human-induced land-cover changes, and related studies are often based on the multi-decadal Landsat archive. However, in areas such as the Tropical Andes, scarce data and the resulting poor signal-to-noise ratio in time series data render the implementation of automated time-series analysis algorithms difficult. The aim of this research was to investigate a novel approach that combines image compositing, multi-sensor data fusion, and postclassifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…We collected a set of land-cover and land-cover change maps generated biannually for the period 1990–2014 in the NEA. They were generated for previous research to monitor long-term forest dynamics with scarce data [70], reporting an overall accuracy above 70%. Specifically, this approach uses the Landsat surface reflectance time-series product [71] to reduce it into cloud-free biennial composites.…”
Section: 3 Methodsmentioning
confidence: 99%
“…We collected a set of land-cover and land-cover change maps generated biannually for the period 1990–2014 in the NEA. They were generated for previous research to monitor long-term forest dynamics with scarce data [70], reporting an overall accuracy above 70%. Specifically, this approach uses the Landsat surface reflectance time-series product [71] to reduce it into cloud-free biennial composites.…”
Section: 3 Methodsmentioning
confidence: 99%
“…However, Refs. [71][72][73] reported that the area assessed has suffered from deforestation in recent years.…”
Section: Global Product Comparisonmentioning
confidence: 99%
“…In recent years, multi-sensor data fusion technology has been widely used in the military and civilian fields [23]. In general, according to the different levels of processing of information sources, multi-sensor data fusion has generally been divided into data-layer fusion, feature-layer fusion, and decision-layer fusion [24].…”
Section: Multi-sensor Data Fusion Technologymentioning
confidence: 99%